La «transición a la democracia» en la Argentina frente a las cristalizaciones de la memoria - Marina Franco (Caravelle)
This article deals with the process leading to democracy in Argentina which took place between the end of the last military dictatorship (1976-1983) and the beginnings of Raul Alfonsin’s democratic government. Our approach is centered upon the problem of violation of human rights commited by the Armed Forces in order to analyze the process which lead to the sentences of those responsible.